Space___Between: Remnants of a city as catalysts for change - Calanchini González Cos, Juan Carlos (2021)
It all starts with a question… Or perhaps too many. What can be done with the remnants of any given city? Can they be transformed to create a shared, cohesive, and productive urban environment? Understanding that the city is an unfinished, ever-productive, ever-dynamic and ever-changing project, it cannot be ignored that, while transforming specific zones in a city, other zones get abandoned in the developing process for an undefined period of time. These urban slivers are often seen as negative spaces rather than positive ones; I will focus on the important indeterminacy and uncertainty that they possess. This research project will centre on these unoccupied, abandoned, or underutilized places within the city, analysing different dynamics of reintegration into the city’s fabric while incorporating Michael Foucault’s heterotopias, as well as some case studies in Gordon Matta-Clark’s œuvre to the discourse. Specifically, I argue that terrain vagues, a term first coined by Ignasi de Solà-Morales i Rubió, and related terms should be seen as site-specific tools for critique and creativity. In order to positively take over any urban void, I address the issue of property, social attachment, and identity to the place, intertwined with the dynamics of architecture and urbanism. I propose to incorporate the concepts of memory and time inherent to these dynamics in order to develop a profound reading of any given site; generate a reinterpretation that can trigger a longstanding change to attain the reinstatement of public property with creative and straightforward approaches; and, then, perform a temporal or permanent, architectonic or artistic intervention, aiming for a new sense of social meaning. In conclusion, this paper sheds new light on the necessity to embrace the opportunities provided by these urban voids. Art and architecture can act as key elements to link people and spaces within a sociocultural context and thus create catalysts for change endowed with meaning.